Implementation of Iconic Card Based Malay Cultural Values in Developing Character Education of Senior High School Students - Juliana, Juliana (Lingual Journal of Language and Culture; Vol 9 No 1 (2020): Lingual: Journal of Language and CultureDO - 10.24843/LJLC.2020.v09.i01.p08, 2020)
The lack of the students ' interest and attention toward the local wisdom values of the local culture is th is research background. The phenomena are due to the absence of interactive media to strengthen character education based on local wisdom in school. The purpose of this research is to create an interactive media based on local wisdom values with the implementation of the iconic card to strengthen the local wisdom values of Malay culture which is useful to build students ’ character education. The research use d a qualitative descriptive method with social anthropolinguistics approach. The subject of this research was students of Nurul Hasanah Senior High School, Medan. The data were collected through field observation, interview, and documentation. The results showed that the iconic card might be used as a media to teach Malay wisdom values with the use of the Pak Belalang icon and Malay pantun. Pantun in this research has local wisdom values of Malay culture such as moral, ethical and norm values. Therefore, it can be concluded that the iconic card can be used as media in strengthening the local wisdom values of Malay culture that useful for students' character education.